EFEKTIVITAS PEMBERIAN PAKAN TAMBAHAN IKAN TERI DALAM PEMELIHARAAN BENIH IKAN KERAPU TIKUS (Cromileptes altivelis) - Tusaban; Achmad, Dewi Shinta (TECHNO-FISH, 2025)
The high cost and difficulty in meeting the nutritional requirements of feed presentfundamental challenges in the cultivation of humpback grouper (Cromileptes altivelis).Supplementary feed in the form of anchovies (Stolephorus sp) is an alternative source of nutrientsto support growth and survival. This study aims to evaluate how anchovy supplementation affectsthe growth rate, survival rate, and feed efficiency in the rearing of juvenile humpback grouper.The study utilized a Completely Randomized Design (CRD) with four treatments, each replicatedthree times. Data obtained from observations were analyzed using ANOVA and the LeastSignificant Difference (LSD) test to identify treatments that showed significant differences.Treatment C yielded the highest daily growth rate at 5.75% and the best absolute length gain of4.03 cm. Treatments B and C showed the highest survival rates, reaching 93.33%, and thehighest feed efficiency, with a value of 0.224. During the research, water temperature ranged from28.17°C to 31.09°C, pH levels were between 7.02 and 8, and salinity ranged from 31.11 to 34.92ppt. The results indicate that adding anchovy feed significantly improves juvenile humpbackgrouper growth and feed efficiency, but does not significantly affect their survival rate.